Solvothermal synthesis of metastable molybdenum, tungsten and vanadium oxides - Sviridova, Tatyana V. (Journal of the Belarusian State University. Chemistry, 2020)
It is shown that under the solvothermal conditions the polycondensation of molybdic, tungstic and vanadic oxoacids yields metastable oxide phases (h-MoO3, h-WO3, xerogel-V2O5 of lamellar structure) in the form of microcrystals 2–10 μm in size, while the hydrates of these oxides formed as the by-products exhibiting conversion as the result of recrystallization during the course of further growing. By changing the concentration of the reaction solution it is possible to exert an effective control over the nucleation to obtain the oxide particles of the similar structure and habitus.